Design, synthesis and docking studies of novel dipeptidyl boronic acid proteasome inhibitors constructed from αα- and αβ-amino acids. Issue 8 (15th April 2016) - Shi, Jingmiao; Lei, Meng; Wu, Wenkui; Feng, Huayun; Wang, Jia; Chen, Shanshan; Zhu, Yongqiang; Hu, Shihe; Liu, Zhaogang; Jiang, Cheng
Graphical abstract: A series of novel dipeptidyl boronic acid proteasome inhibitors constructed from αα and αβ amino acids were designed and synthesized. Abstract: A series of novel dipeptidyl boronic acid proteasome inhibitors constructed from αα- and αβ-amino acids were designed and synthesized. Their structures were elucidated by 1 H NMR, 13 C NMR, LC–MS and HRMS. These compounds were evaluated for their β5 subunit inhibitory activities of human proteasome. The results showed that dipeptidyl boronic acid inhibitors composed of αα-amino acids were as active as bortezomib. Interestingly, the activities of those derived from αβ-amino acids lost completely. Of all the inhibitors, compound22 (IC50  = 4.82 nM) was the most potent for the inhibition of proteasome activity. Compound22 was also the most active against three MM cell lines with IC50 values less than 5 nM in inhibiting cell growth assays. Molecular docking studies displayed that22 fitted very well in the β5 subunit active pocket of proteasome.